O poder judiciário e a implementação da política antitruste no Brasil - Barbosa, Gilmara Maria de Oliveira (2014)
Given the imperative need of improving the relationship between the Judiciary and the antitrust authorities for the promotion of an increasingly efficient competitive environment in Brazil, the study at issue is aimed at analyzing the Judiciary praxis in connection with the national antitrust policy by enforcing judicial control over the administrative decisions rendered by the Administrative Council for Economic Defense – CADE, be it in connection with acts of economic concentration (control over economic structures) or in connection with the administrative procedures themselves (control over the administrative conduct). The work is based on extensive bibliographic references regarding the relevant matter as well as in paradigmatic case law related thereto. Firstly, the study focuses on the concept of antitrust public policies and subsequently presents the national and international fundaments and context that has drawn the attention of the public interest to the defense of the competitive environment. Furthermore, it analyzes the goals and values protected under the Brazilian antitrust policy, proposing a reflection regarding the possibility of characterizing the principles of free competition and free enterprise as fundamental rights. Aiming at investigating the guidelines applicable to the conduct of the private agents involved as enforcers or addressees of the antitrust policy, the work presents the arrangement of rules and procedures which structure the governmental action in the competitive environment, as well as identifies the authorities responsible for the implementation of the competitive policy. Lastly, the study also discusses the international praxis of judicial review of acts and decisions of the antitrust authorities and places a diagnosis of the respective Brazilian scenario, by highlighting the controversial discretion of the decisions rendered by CADE and the restrictions to their judicial review, both under formal and substantive aspects. As a conclusion, the study reveals whether and to which extent the Judiciary has altered or influenced the implementation of the public antitrust policy in Brazil and how the interference of the Judiciary impacts the promotion of fundamental rights.